THE EFFECT OF GIVING CALCIUM SOAP IN THE FEED ON THE PHYSICAL COMPOSITION CARCASSES OF MALE BALI DUCKS - K. L., Parahita; Candrawati, D. P. M. A.; Puspani, E. (Jurnal Peternakan Tropika, 2022)
Giving the proper ration is excpected the physical quality carcass composition. This study aimed to determine the effect of giving calcium soap in the feed on the physical composition carcasses of two weeks male bali ducks. The research used 24 experimental units consisted of 4 treatments and 6 replications with complete random design (RAL) analysis. Each experimental unit consisted of 4 two weeks male bali ducks with homogeneous weight. The treatments were given bali male ducks fed rations without calcium soap (A), (B) 1% calcium soap rations, (C) a ration of 2% calcium soap, and (D) a ration of 3% calcium soap. The variables observed were carcass weight (g/tail), carcass percentage (%), carcass meat percentage (%), carcass bone percentage (%), and percentage of meat fat including the skin (%). Results of this study indicated that the weight of carcass male bali duck given 1% (B), 2% (C) and 3% (D) calcium soap was significantly higher (P<0,05) than control (A). The percentage of duck carcass that given 1%, 2% and 3% calcium soap was non-significant (P>0,05) than control. The percentage of carcass meat given 1%, 2% and 3% calcium soap was significantly higher (P<0,05) than control. The percentage of duck bones given 1%, 2% and 3% calcium soap was non-significant (P>0.05) from control treatment. The percentage of duck meat fat including the skin given 1% calcium soap non-significant (P>0,05) than control, while in treatment 2% and 3% calcium soap was significantly (P<0,05) higher than control. From the results of the study it can be concluded that the addition of calcium soap in rations can increase the weight and the meat percentage of male bali duck carcass. The addition of 2% and 3% calcium soap in rations may reduce the percentage of meat fat including the skin. Keywords: Calcium soap, Bali duck, and Physical composition of carcasses